An Approach to Qualitative Analysis in the Understanding of Cosplay and Crossplayer - Butsainah Adiba Wafa; Luthfi Fathan Dahriyanto (Developmental and Clinical Psychology, 2024)
The term "crossplay" is used to describe an individual who engages in role-play (costume and play) by assuming a character of a different gender than their own in the context of cosplay. This discrepancy in identity frequently gives rise to the labelling and negative perceptions of crossplayers within society. The objective of this research is to gain insight into the self-identity of crossplayers. This research employs a qualitative methodology with a phenomenological approach. The data collection techniques employed were interviews and observation. The subjects of this research were two primary sources and four secondary sources from Yogyakarta. The research employs an interactive model analysis. The findings indicate that each crossplayer has a distinct etiology and motive for engaging in crossplay. However, both groups seek to express themselves freely through crossplay, in conjunction with their closest associates. Crossplay provides a forum for resource persons to explore in order to develop their self-identity